Methylphenidate for the cognitive and neurobehavioural sequelae of traumatic brain injury in adults: a systematic review and meta-analysis - Rees, Jemima L. C.; Saunders, Rachel; Krynicki, Carl R.; Belli, Antonio; Ahmed, Zubair; Di Pietro, Valentina; Stevens, Andrew R. (Frontiers in Neurology, 2025)
IntroductionTraumatic brain injury (TBI) is a leading cause of death and disability globally and is associated with long-term cognitive and neurobehavioural deficits. Methylphenidate has been proposed to address these lasting symptoms, however comprehensive evidence is lacking.MethodsThis systematic review aimed to assess the effects of methylphenidate on multiple cognitive and neurobehavioural domains in adults with TBI. The search conducted across five databases yielded 1,019 results, of which 25 were relevant to this review. Meta-analyses were conducted where homogenous data was available.ResultsSignificant results favouring methylphenidate were recorded by meta-analyses for one of five cognition outcome measures (Trail Making Test A) (p = 0.005, CI [−5.19, −0.91]), as well as the depression domain (p < 0.00001, CI [−0.78, −0.39]) and the fatigue domain (p < 0.00001, CI [−0.98, −0.67]). Insufficient data was available in the aggression, apathy, agitation, memory, motor function, post-concussion syndrome and sleep domains for inclusion in meta-analysis. Qualitative review of evidence in these domains found limited and mixed evidence on the efficacy of methylphenidate, though significant benefits have been demonstrated in these various domains in small, randomised studies. Eleven of the 25 studies were judged as containing some to high risk of bias. However, this review identified supportive evidence for the beneficial effects of methylphenidate to improve depression and fatigue in adults with TBI, with some possible benefits for cognition and other symptoms. Heterogeneity was high and risk of bias was variable across studies, somewhat limiting credibility of results.DiscussionMethylphenidate may enhance the ongoing care of TBI patients, by addressing neurobehavioural and cognitive symptoms simultaneously. Further large-scale and high-quality clinical trials evaluating a comprehensive range of possible benefits to symptoms should be conducted to more conclusively elucidate the potential of methylphenidate for clinical efficacy in TBI.